Analisis Perbandingan Performa Routing Flooding dan Convergecast Pada Wireless Sensor Network - Syifaul Hud'riyah; Rakhmadhany Primananda; Sabriansyah Rizqika Akbar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
Wireless Sensor Network is a collection of a number of nodes arranged in a network. Some types of routing algorithms used in Wireless Sensor Network among its Flooding and Convergecast. Flooding is a routing protocol in wireless sensor networks that use random packet Broadcast on a network. Convergecast is a mechanism for displaying the data flow from many different source nodes to the base station node with a short time. In this study a comparison between routing Flooding with routing Convergecast. This comparison is aimed to find out where routing is better to transmit data. Then to determine the performance of the routing is done testing with some of the parameters used. These parameters are the average backoff, power consumption, latency, frame and number Tx Rx frames. The number of nodes used in testing are 5, 10, 15, 20 and 25. In the testing that was done routing Flooding as much as 5, 10, 15, 20, 25, a mobile node has a backoff value with the average value of 0.0034 ms represents the best and the value of backoff protocol has a value of 0.0024 ms Convergecast. Convergecast Flooding protocol and has a value of power consumption with the average value of the same is 94.1 mW. To value is best latency routing Convergecast with an average value of 0.022 ms while routing Flooding average value of 0,015 ms. For the value of Tx frame number is best routing Convergecast with an average value of 6.8 ms and for routing Flooding with an average value of 1.0 ms. While the value of the frame number Rx is best routing Convergecast with an average value of 15.4 ms routing Flooding with an average value of 2.8 ms